Development of a Biology Learning Outcome Instrument on Ecosystem and Its Interactions Using an Inquiry - Lathifah Turrohmah; Vikto Agus Wibowo; Tago Alam (Penerbit Goodwood, 2026)
Purpose: This study aims to develop and examine the psychometric quality of a biology learning outcome instrument covering the cognitive, affective, and psychomotor domains on the topic of ecosystems and their interactions through an inquiry learning approach for tenth-grade senior high school students.Methodology: The study employed a research and development design using a simplified developmental model comprising instrument planning, blueprint development, expert validation, field testing, and empirical analysis. The instrument was validated by two evaluation experts and subsequently tested on 30 tenth-grade students at a public Islamic senior high school in Metro City, Lampung, using a 30-item multiple-choice cognitive test, an affective observation sheet, and a psychomotor rubric.Results: Expert validation produced a mean feasibility score of 84.5 percent, categorized as good. Empirical testing showed that ten of the thirty cognitive items were valid, with a KR-21 reliability coefficient of 0.731, indicating high reliability, while the affective and psychomotor instruments produced Cronbach alpha coefficients of 0.891 and 0.724 respectively. Item difficulty and discrimination analyses indicated a predominance of moderate-difficulty items with good to very good discrimination power.Conclusions: The developed instrument is feasible for measuring biology learning outcomes through an inquiry approach, although the cognitive component requires item revision to raise its validity rate.Limitations: The study was restricted to a single class and a single topic, limiting generalizability.Contributions: This study contributes a validated, ready-to-use multidimensional assessment instrument and empirical evidence that can guide biology teachers and instrument developers in designing inquiry-based evaluation tools for ecosystem-related content.